Indonesian grade 11 students’ conceptual difficulties with measures of central tendency: An nvivo-assisted qualitative study of representativeness, visualization, and decision making - Puput Indriyani Nur haeni; Mohamad Gilar Jatisunda (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Conceptual understanding is essential in statistics learning, especially measures of central tendency, because it supports students’ ability to represent, interpret, and make data-based decisions. Aims: This study identifies patterns of students’ conceptual difficulties in measures of central tendency across basic concepts, data visualization, data interpretation, and decision making. Methods: A qualitative descriptive case study involved 33 eleventh-grade students from a public senior high school. Data came from a written test and semi-structured interviews with six purposively selected students. Responses were analyzed using NVivo-assisted inductive open coding. Trustworthiness was supported through data-source triangulation, peer debriefing, and an audit trail. Result: Twenty-two initial codes were synthesized into four themes: understanding basic concepts, data visualization, data interpretation, and Application and decision making. Difficulties were most prominent in viewing central tendency as a representative value, constructing histograms and line plots, and justifying contextual decisions. Common misconceptions included computing the mean as “total frequency ÷ number of categories” and treating histogram tasks as table rewriting rather than graph construction. Overall, the pattern suggests a plausible progression linking conceptual understanding with representational and interpretive demands. Conclusion: Students’ difficulties are interrelated and conceptually driven; instruction should emphasize representativeness, multiple representations, and evidence-based reasoning.